Pengaruh Brand Image, Brand Trust dan Kualitas Produk terhadap Keputusan Pembelian pada Sanjai Nita di Bukittinngi (Studi Kasus pada Pengguna dan Pelanggan Sanjai Nita) - Yuli Angraini (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This research is titled The Influence of Brand Image, Brand Trust and Product Quality on the Purchase Decision of NITA Sanjai Crackers in Bukittinggi. The purpose of this study is to determine the influence of brand image, brand trust and product quality on purchasing decisions in NITA sanjai crackers in Bukittinggi. The sample taken was 60 respondents using Ferdinand's formula. The data analysis methods used by the author in this study are validity test, reliability test, classical test, normality test, heterokesdaticity test, mulicolineity test, correlation analysis, multiple regression analysis, partial test, simultaneous test and determination test. The research conducted by the author is a research with a quantitative method. From the analysis that has been carried out, the author finds that there is a positive and insignificant influence between brand image variables on purchase decision variables. There is a positive and significant influence between the brand trust variable on purchase decisions. There is a positive and significant influence between product quality variables on purchasing decisions. There is a positive and significant influence between brand image, brand trust and product quality variables on purchase decisions.